Segmental Spinal Anaesthesia with Sequential Hyperbaric and Isobaric Ropivacaine for Laparoscopic Hysterectomy in a High-risk Kyphoscoliosis Patient: A Case Report - Anupama Kumari; Jigisha Mehta; Sara Mary Thomas (Journal of Clinical and Diagnostic Research, 2025)
Anaesthesia management in patients with multiple comorbidities and anatomical challenges poses significant perioperative risks when scheduled for complicated surgeries. This case report highlights the successful application of sequential hyperbaric and isobaric ropivacaine in segmental spinal anaesthesia in a 65-year-old female patient with kyphoscoliosis and multiple comorbidities undergoing Laparoscopic-Assisted Vaginal Hysterectomy (LAVH). Her comorbidities included bronchial asthma, type 2 diabetes mellitus, hypertension, hypothyroidism, ischaemic heart disease, and early-stage Chronic Kidney Disease (CKD). Her anaesthetic management was further complicated by a challenging airway (Mallampati grade III, limited mouth opening, and restricted neck movements), uncontrolled blood pressure, elevated blood glucose levels, and compromised renal status. Considering her complex medical profile and anatomical challenges, segmental spinal anaesthesia was chosen as the primary anaesthesia modality, with general anaesthesia as a fallback plan and the necessary instruments readily available. Surgical anaesthesia was achieved with two-drug sequential segmental spinal anaesthesia administered in the T9-T10 intervertebral space using hyperbaric ropivacaine 0.75% (9 mg) and isobaric ropivacaine 0.75% (11.25 mg), with a 60-second interval between the two drug injections. The operative course was uneventful, requiring only mild sedation and analgesia. A single episode of intraoperative hypotension and bradycardia was managed promptly. The patient experienced excellent postoperative analgesia and required intravenous analgesics eight hours after the surgery. She was later discharged uneventfully on the fourth postoperative day. This case demonstrates the feasibility and safety of using sequential hyperbaric and isobaric ropivacaine for segmental spinal anaesthesia in high-risk patients with anatomical challenges, offering a viable alternative to General Anaesthesia (GA) in complex surgical scenarios.